Application of Solar Thermal Cooling System Driven by Low Temperature Heat Source in China. (May 2015) - He, Tao; Zhang, Xinyu; Wang, Conghui; Wang, Min; Li, Bojia; Xue, Ning; Shimizu, Kazuo; Takahashi, Kenji; Wu, Youyi
Abstract: Solar thermal cooling is one of the best promised technologies to get cooling from the sun. The main obstacle to promoting this technology is its high initial cost and low efficiency. Nowadays more and more evacuated tube collectors can work at temperature up to 90˚C with efficiency no less than 40%. At the same time, absorption chillers driven by heat medium at lower than 90 ˚C are emerging in China. This paper presents a novel solar thermal cooling system applied in a typical office building with 50RT absorption chillers and normal Chinese evacuated tube collectors in China. This system can store both heating and cooling simultaneously. The system has been modeled and optimized with the TRNSYS software. Then the model and optimization results have been verified through validation tests. The energy efficiency and economic performance of the system has also been analyzed based on the simulation results. Results show that the annual average efficiency of collectors is37.6%, and the solar fraction of the system in summer and winter is respectively 0.76 and 0.38.Simulation results also show that compared with traditional cooling and heating system, 66% of primary energy consumption could be reduced, and the net present value (NPV) of life cycle cost for the novel system is 24.4% less. The novel solar thermal cooling system is a much better way to substitute traditional systems with 5yearsof dynamic payback period.